Analysis of heat and mass transfer in the manufacturing process of instant soy milk using a laboratory scale spray dryer - Nely Ana Mufarida; Asroful Abidin (Universitas Muhammadiyah Metro, 2021)
The events that occur during the drying include heat and mass transfer processes. So based on this, this research will discuss